Pengaruh Kompetensi Profesional Guru Pendidikan Agama Kristen dalam Desain Kurikulum terhadap Efektivitas Belajar Siswa di SMP Swasta Wiyata Dharma Medan - Sembiring, Aristar Setiawan; Pasaribu, Andar Gunawan; Siregar, Nurliani (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2025)
Professional competence is the ability to master material, learn broadly and in depth which enables guiding students to meet the competency standards set out in national education standards. Christian religious education is an effort to prepare people to believe, understand and practice the Christian religion itself. The aim of this research is to determine the influence of the professional competence of Religious Education teachers on the effectiveness of student learning at SMP Swasta Wiyata Dharma Medan.The operational definition is the independent variable, namely Professional Competence of Religious Education Teachers (X) and the dependent variable is Student Learning Effectiveness (Y). This type of research method is quantitative research, namely by providing numbers from data that has been obtained from research results. Data collection techniques are observation, questionnaires and data analysis using normality tests, linearity tests, correlation tests and hypothesis tests.The results of the research show that there is a significant correlation between the variable teacher professional competence (X) and student learning effectiveness (Y) at Wiyata Dharma Private Middle School, Medan.